GAMBARAN FAKTOR RISIKO PENYAKIT PERIODONTAL PADA ANAK JALANAN DENGAN EKS ANAK JALANAN DI KOTA SEMARANG (STUDI PADA ANAK JALANAN LEPAS, ANAK PENDAMPINGAN RPSA X, DAN ANAK PGOTBALAI REHABILITASI SOSIAL Y KOTA SEMARANG) - Anggit Vikasari; Agus Suwandono; Henry Setyawan Susanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Semarang City Health Office in 2015 found as many as 681 new cases of gum and periodontal diseases that occur in children aged 5-14 years. Periodontal disease in children by its age certainly does not recognize social status like street children or ex street children. Street children generally have poor dental hygiene degree who are influenced by maintenance of oral hygiene. The purpose of this study is to identify and describe the risk factors of periodontal disease between street children and ex street children in Semarang. This research is descriptive quantitative-qualitative method with cross-sectional design study. The results show that are proportion frequencies of risk factors in respondents. From 60 respondents are known that 23,3% of 14 years old, 51,7% students of elementary school, 71,7% have job,100% have parents with low income, 50% have good plaque status, 56,7% have moderate OHI-S status, and 40% have moderate CPITN status. Respondents are advised to brushing their teeth or using mouthwash regularly also take control for intake consumption, do not smoke, do not using drugs-psychotropic substances and drinking alcohol.